Relationship between intestinal microbiota and blood pressure - Alfredo Enrique Arredondo Bruce; Gustavo Guerrero Jiménez; Alfredo Enrique Arredondo Rubido (Centro Provincial de Información de Ciencias Médicas, 2019)
The association of Firmicutes and Bacteroidetes intestinal microbes with hypertension has been demonstrated, including people sensitive to salt. Also, the microbiota decrease due to antibiotics can increase or diminish the blood pressure according to the genotype influence. Some arguments on the topic are communicated in this work and, also, it is explained how the biological function of probiotics can also be the result of epigenetics modifications, related, to some extent, to the micro-RNA, and how the nutrients fermentation products due to microbiota can influence in blood pressure regulating the energy expense, intestinal metabolism of catecholamines and gastrointestinal and renal ionic transportation, and with it the sensibility to salt. Lastly, it is concluded that the beneficial or deleterious effect of intestinal microbiota on blood pressure is a consequence of different variables, including genetics and epigenetics variables, as well as lifestyle and use of antibiotics.